Mechanism Of Paying Compensation In Land Acquisition To Land Owners - Akmal Siregar, Lasro; Pakpahan, Kartina; Fitriyani Pakpahan, Elvira (International Journal of Educational Research & Social Sciences, 2022)
The land issue is an issue that affects the most basic rights of the people. Because it has a social function other than economic value, so that individual interests on land are sacrificed for common purposes. The purpose of this study is to analyze the payment of compensation for land acquisition in cash and in kind, to identify and analyze the land acquisition process based on Law no. 2 of 2012, as well as explaining the concept and its provisions. To investigate and analyze. This is done by searching for relevant regulations and literature through the search for library materials as a starting material for investigation, using normative legal procedures for problem analysis. Depending on the issue being investigated, the matter will be carried out to analyze the legal regulations in the area of ​​implementing the release of property rights. The results of the examination show that the payment of compensation for the purchase of land can be in the form of cash or non-cash. Change of money, land, resettlement. The land acquisition process that is being developed based on Law no. 2 of 2012 through three stages: The process of planning, compiling and implementing remuneration, concepts and regulations in land acquisition must be carried out in accordance with laws and regulations so that it is fair and does not harm the government or land owners.